Respuesta :

Answer:

[tex] \int_{-\infty}^0 5 e^{60x} dx = \frac{1}{12}[e^0 -0]= \frac{1}{12}[/tex]  

Step-by-step explanation:

Assuming this integral:

[tex] \int_{-\infty}^0 5 e^{60x} dx[/tex]

We can do this as the first step:

[tex] 5 \int_{-\infty}^0 e^{60x} dx[/tex]

Now we can solve the integral and we got:

[tex] 5 \frac{e^{60x}}{60} \Big|_{-\infty}^0 [/tex]

[tex] \int_{-\infty}^0 5 e^{60x} dx = \frac{e^{60x}}{12}\Big|_{-\infty}^0 = \frac{1}{12} [e^{60*0} -e^{-\infty}][/tex]

[tex] \int_{-\infty}^0 5 e^{60x} dx = \frac{1}{12}[e^0 -0]= \frac{1}{12}[/tex]  

So then we see that the integral on this case converges amd the values is 1/12 on this case.

Space

Answer:

The improper integral converges.

[tex]\displaystyle \int\limits^0_{- \infty} {5e^{60x}} \, dx = \frac{1}{12}[/tex]

General Formulas and Concepts:
Calculus

Limit

Limit Rule [Variable Direct Substitution]:                                                         [tex]\displaystyle \lim_{x \to c} x = c[/tex]

Differentiation

  • Derivatives
  • Derivative Notation

Derivative Property [Multiplied Constant]:                                                       [tex]\displaystyle \frac{d}{dx} [cf(x)] = c \cdot f'(x)[/tex]

Derivative Rule [Basic Power Rule]:

  1. f(x) = cxⁿ
  2. f’(x) = c·nxⁿ⁻¹

Integration

  • Integrals

Integration Rule [Reverse Power Rule]:                                                           [tex]\displaystyle \int {x^n} \, dx = \frac{x^{n + 1}}{n + 1} + C[/tex]

Integration Rule [Fundamental Theorem of Calculus 1]:                                 [tex]\displaystyle \int\limits^b_a {f(x)} \, dx = F(b) - F(a)[/tex]

Integration Property [Multiplied Constant]:                                                     [tex]\displaystyle \int {cf(x)} \, dx = c \int {f(x)} \, dx[/tex]

Integration Method: U-Substitution

Improper Integral:                                                                                             [tex]\displaystyle \int\limits^{\infty}_a {f(x)} \, dx = \lim_{b \to \infty} \int\limits^b_a {f(x)} \, dx[/tex]

Step-by-step explanation:

Step 1: Define

Identify.

[tex]\displaystyle \int\limits^0_{- \infty} {5e^{60x}} \, dx[/tex]

Step 2: Integrate Pt. 1

  1. [Integral] Rewrite [Integration Property - Multiplied Constant]:             [tex]\displaystyle \int\limits^0_{- \infty} {5e^{60x}} \, dx = 5 \int\limits^0_{- \infty} {e^{60x}} \, dx[/tex]
  2. [Integral] Rewrite [Improper Integral]:                                                     [tex]\displaystyle \int\limits^0_{- \infty} {5e^{60x}} \, dx = \lim_{a \to - \infty} 5 \int\limits^0_{a} {e^{60x}} \, dx[/tex]

Step 3: Integrate Pt. 2

Identify variables for u-substitution.

  1. Set u:                                                                                                         [tex]\displaystyle u = 60x[/tex]
  2. [u] Differentiate [Derivative Properties and Rules]:                                 [tex]\displaystyle du = 60 \ dx[/tex]
  3. [Bounds] Swap:                                                                                         [tex]\displaystyle \left \{ {{x = 0 \rightarrow u = 0} \atop {x = a \rightarrow u = 60a}} \right.[/tex]

Step 4: Integrate Pt. 3

  1. [Integral] Rewrite [Integration Property - Multiplied Constant]:             [tex]\displaystyle \int\limits^0_{- \infty} {5e^{60x}} \, dx = \lim_{a \to - \infty} \frac{1}{12} \int\limits^0_{a} {60e^{60x}} \, dx[/tex]
  2. [Integral] Apply Integration Method [U-Substitution]:                             [tex]\displaystyle \int\limits^0_{- \infty} {5e^{60x}} \, dx = \lim_{a \to - \infty} \frac{1}{12} \int\limits^0_{60a} {e^{u}} \, du[/tex]
  3. [Integral] Apply Exponential Integration:                                                 [tex]\displaystyle \int\limits^0_{- \infty} {5e^{60x}} \, dx = \lim_{a \to - \infty} \frac{1}{12} e^u \bigg| \limits^0_{60a}[/tex]
  4. Evaluate [Integration Rule - Fundamental Theorem of Calculus 1]:       [tex]\displaystyle \int\limits^0_{- \infty} {5e^{60x}} \, dx = \lim_{a \to - \infty} \frac{1 - e^{60a}}{12}[/tex]
  5. [Limit] Evaluate [Limit Rule - Variable Direct Substitution]:                     [tex]\displaystyle \int\limits^0_{- \infty} {5e^{60x}} \, dx = \frac{1 - e^{60(-\infty)}}{12}[/tex]
  6. Rewrite:                                                                                                     [tex]\displaystyle \int\limits^0_{- \infty} {5e^{60x}} \, dx = \frac{1}{12} - \frac{1}{12e^{60(\infty)}}[/tex]
  7. Simplify:                                                                                                     [tex]\displaystyle \int\limits^0_{- \infty} {5e^{60x}} \, dx = \frac{1}{12}[/tex]

∴ the improper integral equals [tex]\displaystyle \bold{\frac{1}{12}}[/tex]  and is convergent.

---

Learn more about improper integrals: https://brainly.com/question/14413972

Learn more about calculus: https://brainly.com/question/23558817

---

Topic: AP Calculus BC (Calculus I + II)

Unit: Integration